Activation of Veratridine Sensitive Sodium Channels, But not Electrical Field Stimulation, Dilates Porcine Retinal Arterioles with Preserved Perivascular Tissue. (2nd November 2017) - Kratholm, Nils M.; Jensen, Peter Skov; Kringelholt, Sidse; Simonsen, Ulf; Bek, Toke
ABSTRACT: Purpose : Disturbances in retinal blood flow are a prominent feature of vision threatening retinal diseases. The regulation of tone in retinal resistance vessels involves the perivascular retinal tissue, but it is unknown to what extent neurons or glial cells contribute to the effect. Therefore, the purpose of the present study was to study the contribution of neurons in the perivascular retina to vascular tone during activation of voltage-gated sodium channels with veratridine and electrical field stimulation (EFS). Methods : Porcine retinal arterioles with and without perivascular tissue were mounted in an isometric myograph system for studying the effects of the voltage-gated sodium channel opener veratridine and EFS on retinal vascular tone. Results : Veratridine induced concentration-dependent relaxation of retinal arterioles which was more pronounced in arterioles with preserved perivascular retinal tissue than in isolated vessels. In the presence of this tissue, veratridine-induced relaxation was inhibited by the voltage-gated sodium channel blocker tetrodotoxin and the nitric oxide synthase inhibitor, Nω -Nitro-L-arginine methyl ester (L-NAME), but was unaffected by the inhibition of the cyclo-oxygenase inbitior ibuprofen and by blocking of adenosine receptors with 8-(p-Sulfophenyl)theophylline hydrate (8-PSPT). Electrical field stimulation induced no changes in retinal vascular tone. Conclusions : Sodium channels of neuronal origin are likely to be involved in the regulation of retinal vascular tone. The lack of effect of EFS on retinal vascular tone may be due to the lack of autonomic nerves in the retina.